2021
DOI: 10.3390/foods10020318
|View full text |Cite
|
Sign up to set email alerts
|

Food Choice Determinants and Perceptions of a Healthy Diet among Italian Consumers

Abstract: Healthy food choices are crucial for a healthy lifestyle. However, food choices are complex and affected by various factors. Understanding the determinant factors affecting food choices could aid policy-makers in designing better strategies to promote healthy food choices in the general public. This study aims to evaluate the food choice motivations and to segment consumer groups, according to their food choice motivations, in a sample of 531 Italian consumers (collected by convenience sampling), through offli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 38 publications
8
53
2
2
Order By: Relevance
“…Our results, in terms of health issues regarding TFs, agree with the findings of both reports. Other recent studies found environmental factors, together with health, to be the determinants of choices for Italian consumers [57], and that there is a shift towards healthier diets for Russian adults [58]. These findings were also verified by our results in the case of TFs.…”
Section: Discussionsupporting
confidence: 91%
“…Our results, in terms of health issues regarding TFs, agree with the findings of both reports. Other recent studies found environmental factors, together with health, to be the determinants of choices for Italian consumers [57], and that there is a shift towards healthier diets for Russian adults [58]. These findings were also verified by our results in the case of TFs.…”
Section: Discussionsupporting
confidence: 91%
“…There is relevant confirmation that specific social norms linked to food consumption have a major effect on people's food choices. On the other hand, the globalization of food supply chains has increased the availability and variety of foods, becoming eventually less sustainable, owing to long distances travelled across the globe and/or being available throughout the entire year and not only in the production season [74][75][76].…”
Section: Discriminant Function Analysismentioning
confidence: 99%
“…The “healthy eaters” are a cluster formulated also by other authors as “health-driven consumers”, who try to follow a healthy and balanced diet and choose products of health-promoting values [ 41 ]. Such consumers may be characterized by increased interest in the energy value of food products [ 42 ], and this approach may be associated with the choice of specific food products, as the health-oriented consumers may consciously choose products presenting higher health-promoting value [ 43 ].…”
Section: Discussionmentioning
confidence: 99%